Edukasi tatalaksana awal pada luka bakar di Kecamatan Cempaka Baru, Jakarta Pusat (Education on early management of burns in Cempaka Baru Sub-District, Central Jakarta) - Mukhtar, Diniwati S; Ridwan, Karina A; Qomariyah, Q; Marsiati, Himmi; Luthfiah, Hasna (Buletin Pengabdian, 2022)
Burns can occur anywhere and anytime. However, until now there is no data on burn mortality. This activity aims to provide education on the initial management of burns in the community of Cempaka Baru Sub-District, Central Jakarta. The methods used are seminars and discussions using Powerpoint slides, as well as pre-test and post-test questionnaire instruments. Results: there were 3 groups of participants, consisting of 4 people (13.3%) young adults (age 15-30 years), 9 middle adults (age 31-50 years), or 30%, and 17 older adults (age 50 years). years) or 56.7%. There was a significant increase in participants' knowledge after the seminar, the lowest pre-test score was 20 and the lowest score was 40 in the post-test. There was an increase in the mode value or the majority value of the participants from the pre-test, which was 80 to 100 in the post-test. Then there was an increase in the average score of participants from 75.12 in the pre-test to 87.94 in the post-test (p = 0.00). After being given education, the results of data analysis still showed an increase in knowledge with significant results, namely the value of p = 0.00 (p 0.05). In conclusion, the increase in participants' knowledge about burns is better than before.